2007
DOI: 10.1007/s00101-007-1250-5
|View full text |Cite
|
Sign up to set email alerts
|

Intraartikuläre Bupivacaingabe bei Hüftgelenkarthroskopie

Abstract: The effect of intra-articular bupivacaine on postoperative pain following arthroscopy has been intensively studied for the knee joint but no data are currently available for the hip joint. The aim of the present prospective, randomized and double-blind study was to evaluate a possible effect of intra-articular bupivacaine on postoperative pain intensity following hip arthroscopy. A total of 26 patients were included: 13 received 20 ml of 0.25% bupivacaine through the trocar at the end of surgery and 13 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Intra-articular bupivacaine (injection of 20 ml 0.25% bupivacaine (50 mg) resulted in significant lower mean VAS scores and a decreased use of rescue medication in the first 20 h postoperatively when compared to placebo (injection of 20 ml 0.9% NaCl solution) in a small study of 26 patients [15]. Unfortunately, no power calculation was performed in this trial.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intra-articular bupivacaine (injection of 20 ml 0.25% bupivacaine (50 mg) resulted in significant lower mean VAS scores and a decreased use of rescue medication in the first 20 h postoperatively when compared to placebo (injection of 20 ml 0.9% NaCl solution) in a small study of 26 patients [15]. Unfortunately, no power calculation was performed in this trial.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported the outcomes of intra-articular infiltration directly after hip arthroscopy [11, 15, 16]. Patients receiving intra-articular bupivacaine had significantly lower VAS scores compared to a placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-articular injections have been used in adults during a multitude of diagnostic and therapeutic procedures such as knee, hip, shoulder, wrist, and ankle arthroscopy; relocation of anterior shoulder dislocations; total knee arthroplasty; and total hip arthroplasty. Although the adult literature has been inconsistent 6,7 , intra-articular injections have demonstrated an analgesic benefit during orthopaedic-related procedures [8][9][10][11][12][13][14][15][16][17][18][19] . The efficacy of intra-articular injections in children has not been well studied.…”
mentioning
confidence: 99%
“…In a systematic review of intra-articular injections during arthroscopic knee surgery, intra-articular injections resulted in a weighted mean difference in visual analog scale (VAS) pain scores of 11 mm (95% CI, 7 to 17 mm; p < 0.05) as well as a 10% to 40% reduction in supplemental analgesic requests 5 . There is also evidence that, when administered alone, single-shot intra-articular local anesthetic injections are significantly more effective for managing procedure-related pain than saline solution injections or no injections during anterior cruciate ligament (ACL) reconstruction 28 , total knee arthroplasty 8 , and arthroscopic knee [9][10][11][12][13][14][15][16] , hip 17 , wrist 18 , and ankle 19 surgery. Our subjects who received intra-articular bupivacaine required a significantly lower opioid dose postoperatively (from arrival in the post-anesthesia care unit to discharge) than did patients in the control group.…”
mentioning
confidence: 99%